Study of Natural Cytotoxicity Receptors in Patients with HIV/AIDS and Cancer: A Cross-Sectional Study - Orlando Nascimento Terra Junior; Gabriel de Carvalho Maldonado; Guilherme Rohem Alfradique; Vinicius da Cunha Lisboa; Adriano Arnóbio; Dirce Bonfim de Lima; Hilda Rachel Diamond; Maria Helena Faria Ornellas de Souza (The Scientific World Journal)
The NCR receptors play a fundamental role in the cytotoxicity mediated by NK cells against tumor cells. In the current study, we investigated possible HIV/AIDS-related changes in the expression of the NCR receptors comparing healthy donors, HIV/AIDS patients, and HIV/AIDS patients with cancer (HIV/AIDSWC). The NCRs were quantified in NK cells (NKdim and NKbright) and T lymphocytes from peripheral blood samples by flow cytometry. We found a significant decrease in the frequency of NK cells expressing NKp46 in HIV/AIDS group (p=0.0012). There was a decrease in the frequency of NK cells expressing NKp46 in the HIV/AIDSWC group; however, this was not statistically significant. We found a significant decrease in the frequency of NK cells expressing NKp30 in the HIV/AIDS group (p=0.0144). There was a decrease in the frequency of NK cells expressing NKp30 and in the HIV/AIDSWC group, but this was not statistically significant. There were no changes in the distribution of NK cells and their subtypes in both groups.